2006
DOI: 10.1007/s10549-006-9176-1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of breast cancer using volatile biomarkers in the breath

Abstract: We evaluated a breath test for volatile organic compounds (VOCs) as a predictor of breast cancer. Breath VOCs were assayed in 51 asymptomatic women with abnormal mammograms and biopsy-proven breast cancer, and 42 age-matched healthy women. A fuzzy logic model predicted breast cancer with accuracy superior to previously reported findings. Following random assignment to a training set (64) or a prediction set (29), a model was constructed in the training set employing five breath VOCs that predicted breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
150
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(158 citation statements)
references
References 10 publications
5
150
0
3
Order By: Relevance
“…Our study showed that compared with lung squamous cell carcinoma, these VOC levels were significantly higher in lung adenocarcinoma (17). Breath analysis was used to detect not only lung cancer but also breast cancer (18,19) and tumors of the head and neck (20). Regretfully, there were no related reports to date available on the diagnosis of HCC.…”
Section: Introductionmentioning
confidence: 76%
“…Our study showed that compared with lung squamous cell carcinoma, these VOC levels were significantly higher in lung adenocarcinoma (17). Breath analysis was used to detect not only lung cancer but also breast cancer (18,19) and tumors of the head and neck (20). Regretfully, there were no related reports to date available on the diagnosis of HCC.…”
Section: Introductionmentioning
confidence: 76%
“…Factors affecting the great variability in the composition of human breath include physical condition, general health of the subject, food intake, environmental influences and overall lifestyle (Amann et al, 2004;Libardoni et al, 2006). (Wehinger et al, 2007), acetaldehyde , heptanal (Phillips et al, 1999a,b;Deng et al, 2004a,b;Phillips et al, 2006); hexanal (Phillips et al, 1999a,b;Deng et al, 2004a,b) Ketones 1-Phenylethanone (Phillips et al, 1999a,b) Hydrocarbons Benzene (Yu et al, 2005;Phillips et al, 1999a,b;Poli et al, 2005); toluene (Poli et al, 2005); styrene (Yu et al, 2005;Phillips et al, 1999a,b;Poli et al, 2005); xylenes isomers (Phillips et al, 1999a,b;Poli et al, 2005); trimethylbenzenes isomers (Phillips et al, 1999a,b;Poli et al, 2005); propylbenzene (Yu et al, 2005;Phillips et al, 1999a,b); ethylbenzene (Poli et al, 2005) 2-Methylheptane (Phillips et al, 1999a,b); 3-methylnonane (Phillips et al, 1999a,b); 3-methyloctane (Phillips et al, 1999a,b); 2-methylpentane (Poli et al, 2005); 2,2,4,6,6-pentamethylheptane (Phillips et al, 1999a,b;Poli et al, 2005); 2,4-dimethylheptane (Phillips et al, 1999a,b); pentane (Poli et al, 2005); heptane (Poli et al, 2005); octane (Poli et al, 2005); decane (Yu et al, 2005;Phillips et al, 1999a,b;Poli et al, 2005); undecane (Yu et al, 2005;Phillips et al, 1999a,b); methylcyclopentane (Phillips et al, 1999a,b); isoprene (Phillips et al, 1999a,b;…”
Section: Endogenous Volatile Markers and Their Clinical Applicationsmentioning
confidence: 99%
“…It is a major cause of death among adult and its incidence is increasing globally. A number of studies have been carried out in order to characterize substances in breath samples from patients with and without lung cancer (O'Neill et al, 1988;Petri et al, 1988;Phillips et al, 1999a,b;Deng et al, 2004a;Poli et al, 2005;Yu et al, 2005;Phillips et al, 2006). In 1988, two groups of researchers separately reported some VOCs as potential lung cancer marking substances (O'Neill et al, 1988;Petri et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Thousands of VOMs in trace amounts are present in human breath [12][13][14][15][16] and different studies have shown that the VOMs profile in patients with lung cancer can be discriminated from those of healthy subjects [12,17,18]. Urine has been the preferred biological fluid since compounds are concentrated by the kidney before excretion [19].…”
Section: Introductionmentioning
confidence: 99%